Evergreen broadleaf forest transition zone changes in Japan from 1961 to 2008 detected by aerial ortho-photos. (June 2016) - Nakazono, Etsuko; Tanaka, Nobuyuki; Yasuda, Masatsugu; Daimaru, Hiromu; Takeuchi, Wataru
Abstract: In order to detect the distribution change of evergreen broad-leaved trees (EBTs) in a old-growth forest on the transitional zone of cool-temperate and warm-temperate zones, we used the ortho-photo data conversed from the aerial photos. Comparing the crown map of EBTs in the 1-ha verification plot with the ground truth data of individual tree inventory, 14 out of 17 (82%) upper layer trees were found to be visually read on the aerial photo We chose two indices for detecting the distribution change of EBTs, crown number and total crown area. We made crown maps of the 20-ha plot based on ortho-photos in 1961, 1975, 1985, 2003, 2005 and 2008, and calculated crown number and total crown area for each photos. The crown number increased at a rate 0.18/year/ha from 1961 to 2000's, and total crown area also increased at a rate 0.21% for the 20-ha plot. The total crow area increase was highly probable because errors of area in orthophotos were smaller than secular changes of the area.